Homeostatic imbalance of regulatory and effector T cells due to IL-2 deprivation amplifies murine lupus - Humrich, Jens Y. (National Academy of Sciences, 2009)
The origins and consequences of a regulatory T cell (Treg) disorder in systemic lupus erythematosus (SLE) are poorly understood. In the (NZBxNZW) F(1) mouse model of lupus, we found that CD4(+)Foxp3(+) Treg failed to maintain a competitive pool size in the peripheral lymphoid organs resulting in a progressive homeostatic imbalance of CD4(+)Foxp3(+) Treg and CD4(+)Foxp3(−) conventional T cells (Tcon). In addition, Treg acquired phenotypic changes that are reminiscent of IL-2 deficiency concomitantly to a progressive decline in IL-2-producing Tcon and an increase in activated, IFN-γ-producing effector Tcon. Nonetheless, Treg from lupus-prone mice were functionally intact and capable to influence the course of disease. Systemic reduction of IL-2 levels early in disease promoted Tcon hyperactivity, induced the imbalance of Treg and effector Tcon, and strongly accelerated disease progression. In contrast, administration of IL-2 partially restored the balance of Treg and effector Tcon by promoting the homeostatic proliferation of endogenous Treg and impeded the progression of established disease. Thus, an acquired and self-amplifying disruption of the Treg-IL-2 axis contributed essentially to Tcon hyperactivity and the development of murine lupus. The reversibility of this homeostatic Treg disorder provides promising approaches for the treatment of SLE.